Seroprevalence of small ruminant lentivirus (SRLV) among small ruminant in foster farm programme, FPV, UPM - Nehru Raju, Veenosha (2017)
Caprine Arthritis-Encephalitis Virus (CAEV) is an incurable disease of goats that has both social and economic impacts. Clinical disease in goats includes encephalitis in kids; chronic arthritis, inflammatory mastitis and progressive respiratory disease in adults. The first reported case of CAE in Malaysia was in year 2010, and another suspected case of CAE was reported in year 2013.Since then no screening was done. Therefore the study was designed to determine the seroprevalance of CAE among goat population in Foster Farm Programme of FPV, UPM and the risk factors associated with this disease. Blood samples were collected from 91 goats via convenient sampling method. The blood serums were used for the competitive ELISA kit to detect antibody towards CAE virus. From the 91 goat samples, 8 samples (8.8%) were positive for CAE.Biosecurity management, source of origin and sex of the animal were important risk factors for the prevalance of CAE in Foster Farm Programme, FPV, UPM. Therefore it can be concluded that seroprevalance of CAE among goat population in Foster Farm Programme, FPV, UPM is low. However control measures such as testing and culling positive animals or segregation of infected animals away from test negative animals can be an important practice for control of horizontal spread among goat population.